2013
DOI: 10.1002/jor.22329
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐body simulation of various falling scenarios for determining resulting loads at the prosthesis interface of transfemoral amputees with osseointegrated fixation

Abstract: Conventionally, transfemoral amputees are treated with a shaft prosthesis fitted over the residual limb. To improve the quality of life of such patients, in particular those with complications relating to conventional attachment (e.g., skin irritation, stump ulcers, and poor motor-control with short stumps), osseointegrated prosthesis fixation implants have been developed and implanted in a limited population of patients. To assess possible damage to the implant/prosthesis during falling scenarios, the loads i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 34 publications
(43 reference statements)
1
19
1
Order By: Relevance
“…Compared to previous findings regarding loads at the osseointegrated prosthesis fixation of the lower extremity during falling [12], the present results illustrate the high risk of fracture. Welke et al reported bending moments at the osseointegrated prosthesis fixation of up to 176 Nm for forward falling on one knee and 187 Nm for falling backwards.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Compared to previous findings regarding loads at the osseointegrated prosthesis fixation of the lower extremity during falling [12], the present results illustrate the high risk of fracture. Welke et al reported bending moments at the osseointegrated prosthesis fixation of up to 176 Nm for forward falling on one knee and 187 Nm for falling backwards.…”
Section: Discussioncontrasting
confidence: 68%
“…Therefore our findings underline the need for the use of a safety element to prevent such fractures as they are related to complicated revision and in the long term a substantial loss of quality of life. The ultimate bending moments observed are considerably below simulated resulting peak moments for dynamic falling scenarios [12], and it should be considered that the duration of load application during falling is range of hundreds of milliseconds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This prosthesis was tested in 5 falling scenarios, with estimated peak loads in all 5 scenarios of a magnitude that could lead to bone fracture. Therefore it is imperative to add a safety‐release element in osseointegrated prosthesis fixation [49].…”
Section: Future Advancesmentioning
confidence: 99%
“…Results gained from these models can be used in the development of prostheses to improve functions of leg prostheses. For example, multibody models are developed for the investigation of interactions taking place in the human body of amputees wearing prostheses during various falling scenarios as it is done in [1].…”
Section: Introductionmentioning
confidence: 99%